Can measures of muscle-tendon interaction improve our understanding of the superiority of Kenyan endurance runners? - Sano, K.; Nicol, C.; Akiyama, M.; Kunimasa, Y.; Oda, T.; Ito, A.; Locatelli, E.; Komi, P. V.; Ishikawa, M. (European Journal of Applied Physiology, 2015)
Purpose: Leg muscle activation profiles and muscle-tendon interaction were studied with eleven internationally high-level Kenyan and eleven national level Japanese distance runners.